Effects of Topography and Geography on Solar Diffuse Fraction Modeling in Taiwan - Chun-Tin Lin; Keh-Chin Chang (Atmosphere, 2024)
A correlation model for the diffuse fraction was recently developed on the basis of a data set obtained in the western part of the Taiwanese mainland. However, it is widely agreed that no existing diffuse fraction correlation model is applicable to all geographical regions and climatic conditions, which is a viewpoint stated from a macro perspective. This study re-justifies this viewpoint through the consideration of a rather small geographical region: Taiwan. The topographic profile of the Taiwanese mainland primarily comprises the high-rise Central Mountain Ranges running from north–northeast to south–southwest, which separate the mainland into eastern and western parts. Furthermore, there are a number of small, remote islands around the Taiwanese mainland. The humidity over the sky dome of these small islands, carried from the moist sea (or ocean) air, is usually greater than that of the Taiwanese mainland. This results in different diffuse fraction patterns between these two geographical regions due to the climatic factor of atmospheric constituents. Two diffuse fraction correlation models for Taiwan were developed using in situ data sets for the eastern part of the Taiwanese mainland and an island in the Penghu archipelago, respectively. In particular, one case considered the topographic effect on modeling the diffuse fraction in Taiwan, while the other considered the geographical effect. Statistical assessments indicate that each correlation model developed in the present study performed better than the previous one developed using the in situ data set for the western part of the Taiwanese mainland, with both applied to the specific site where the data set was used for the model’s development. This work demonstrates the need to consider the effects of topography and geography when modeling the diffuse fraction in Taiwan.